Development of Quality Assurance Automatic Testing Script to Increase Testing Efficiency for Mobile Applications - Abdi Suryadinata Telaga; Lita Eka Wulansari; Naufal Norman Hisyam (Universitas Muhammadiyah Surakarta, 2022)
Consumers increasingly use mobile applications because of the convenience and mobility of use. However, the short application development time and demands to maintain application quality and user satisfaction require a fast and thorough testing process. Many software testers currently test their software manually, causing problems, such as longer test times, inconsistent testing, and the need for human intervention to perform all tests. Therefore, a Quality Assurance Automatic Testing (QA AT) system was created based on mind map diagrams to overcome the earlier problems. QA AT is a script designed to verify the software requirements. The method to develop the QA AT script is as follow. Firstly, develop a Business Process diagram. Secondly, create the Mind Map diagram. Thirdly, build test cases scenarios based on the mind map diagram. Then translate the testing scenarios into testing scripts. Finally, the test scripts run on Katalon Studio platform. The QA AT system transforms the testing process into automated testing. The results show that automated testing can shorten test time by 86%,. Further, reducing human involvement, creating a consistent testing environment, and providing a detailed report.